2019
DOI: 10.3390/ijms20020270
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Inflammatory Cytokine-Induced TP63 Isoform ∆NP63α Signaling Cascade Contributes to Cisplatin Resistance in Human Breast Cancer Cells

Abstract: The mechanisms behind the induction of malignancy and chemoresistance in breast cancer cells are still not completely understood. Inflammation is associated with the induction of malignancy in different types of cancer and is highlighted as an important factor for chemoresistance. In previous work, we demonstrated that the inflammatory cytokine interleukin 1β (IL-1β)-induced upregulation of genes was associated with chemoresistance in breast cancer cells. Here, we evaluated the participation and the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 34 publications
3
28
1
Order By: Relevance
“…The expression of E-cadherin was significantly reduced and showed a close relationship to β-catenin nuclear localization in the tissues of CAC-untreated mice and 5-FU single therapy-treated mice. In agreement with our data, similar results on E-cadherin loss expression and translocation to the nucleus of β-catenin have been reported in breast and pancreatic cancer cells, and this is considered to be a marker of poor survival and resistance to therapies [24,49]. Therefore, these data support our proposal that STAT6 inhibition favors the response to 5-FU by regulating proteins related with cell survival, apoptosis inhibition, and acquisition of aggressive phenotypes in CAC.…”
Section: Discussionsupporting
confidence: 93%
“…The expression of E-cadherin was significantly reduced and showed a close relationship to β-catenin nuclear localization in the tissues of CAC-untreated mice and 5-FU single therapy-treated mice. In agreement with our data, similar results on E-cadherin loss expression and translocation to the nucleus of β-catenin have been reported in breast and pancreatic cancer cells, and this is considered to be a marker of poor survival and resistance to therapies [24,49]. Therefore, these data support our proposal that STAT6 inhibition favors the response to 5-FU by regulating proteins related with cell survival, apoptosis inhibition, and acquisition of aggressive phenotypes in CAC.…”
Section: Discussionsupporting
confidence: 93%
“…In breast cancer, high expression of TP63 coupled with STAT6 has been shown to be associated with longer metastasis-free survival, indicating that TP63 could be involved in inhibiting the migration of breast cancer cells (Papageorgis et al, 2015). By silencing TP63 expression, breast cancer cells acquired increasing resistance to cisplatin, suggesting its role in drug reaction (Mendoza-Rodriguez et al, 2019). SORBS1 is an adaptor protein, and its overexpression inhibits the invasive capacity of tumor cells in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, anandamide-induced degradation of cytoplasmic β-catenin, while CBD relocated β-catenin at the adherens junctions. In both cases the expression of malignant markers in 6D cells was greatly reduced [5,16,17]. In this work, we analyzed the expression of two genes, BIRC3 and TP63, the expression of which was increased by the activation of the IL-1β/IL-1R/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As the above data revealed that addition of CBD to 6D cells caused morphological and molecular changes described in the IL-1β-induced EMT, we investigated if CBD could have a negative effect on the expression of genes and proteins that participate in this process [16,17]. Therefore, qRT-PCR analysis was performed for BIRC3, TP63, and ID1 genes.…”
Section: Cbd Decreased the Expression Of Proteins Related To The Il-1mentioning
confidence: 99%
See 1 more Smart Citation